Myths, state expansion, and the birth of globalization : a comparative perspective - Carlson, Jon D. ([S.l.] : Palgrave Macmillan, 2011)
Myths are important, yet overlooked. Myths, dreams, desires and false information prime the pump of imperial expansion, which explains how new regions of the world get absorbed into the expanding world system. This book explores the role that information plays in the expansion of the state system. High risk, high return behavior subsidizes later 'rational' strategies. The Northwest Passage, Prester John, West African rivers of gold, and Marco Polo's silver-roofed land of Zipangu all provide examples. Not merely an artifact of history, accurate information acquisition and dissemination continues to be relevant, as myths still drive markets and political decision-making.
Keywords: Imperialism; Nation-state and globalization; State, The